Using scents to connect to intangible heritage : engaging the visitor olfactory dimension : three museum exhibition case studies - Miotto, Laura (2020)
Olfactory experiences are powerful triggers of personal memories and can play an important role in connecting audiences to intangible heritage. This is recognized by museums seeking to move beyond the dominant visuocentric exhibition paradigm, broadening the spectrum of sensorial stimuli on offer. However, the delivery of olfactory experiences in a museum presents important and unique challenges, largely related to the odorant's physical nature, which impose constraints to the design of experiences that can reach the visitor with impact and efficacy. Here, we present an olfactory delivery device designed to address these issues, which was prototyped and implemented over a 10-year period as an integral element of a display dedicated to the culinary heritage of Singapore. The device was also utilized in two other exhibitions, with radically different purposes: in one case as an element of the indigenous natural and cultural heritage, and in the other as a comparison tool to provide an intuitive illustration of progress. The diverse subject matters covered, and the different approaches to the delivery of olfactory stimuli demonstrate the versatility of the olfactory device in a range of exhibit settings. The case studies presented indicate that olfactory experiences can be effectively integrated in local museums, but their inclusion demands additional processes and specific consideration. Growing interest in this area of exhibition design, consistent with a global trend to transform museums into multisensory environments, makes this an important field for further research.